2012
DOI: 10.1007/s00277-012-1425-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD39 expression on CD4+ T lymphocytes has clinical and prognostic significance in chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) cells depend on their microenvironment for proliferation and survival. Ectonucleotidase CD39 has anti-inflammatory properties as it hydrolyzes proinflammatory extracellular ATP, generates anti-inflammatory adenosine, and also protects regulatory T cells from ATP-induced cell death. In this study, we investigated the clinical significance of CD39 expression on CD4(+) T cells in 62 patients with CLL as well as its compartmental regulation and explored the possible mechanisms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
4
25
0
1
Order By: Relevance
“…CD39 expressed on Tregs was reported to inhibit NK activity and promote hepatic metastatic tumor growth [36]. The increased expression of CD39 in CD4 + T cells was related to poorer prognosis [37]. We also found high expression of CD39 in aTreg cells from NCSLS patients.…”
Section: Discussionsupporting
confidence: 52%
“…CD39 expressed on Tregs was reported to inhibit NK activity and promote hepatic metastatic tumor growth [36]. The increased expression of CD39 in CD4 + T cells was related to poorer prognosis [37]. We also found high expression of CD39 in aTreg cells from NCSLS patients.…”
Section: Discussionsupporting
confidence: 52%
“…Our data show a pathological T‐cell profile already at the MBL stage, indicating that B‐cells begin to exhibit immunosuppressive function very early in the course of tumorigenesis. We found that MBL patients had an expanded compartment of highly suppressive CD39+ Treg correlating with a significantly more suppressive regulatory function, while at this stage T‐effector function only slightly deviated from healthy controls. As the T‐cell deficiencies in MBL appeared to be rather slight, antitumor responses may not be completely blunted by enhanced immunosuppression at this stage.…”
Section: Discussionmentioning
confidence: 72%
“…They suggested that CD39/adenosine pathway could contribute to “T-cell anergy” in tumors. In chronic lymphocytic leukemia, levels of circulating CD4 + CD39 + T cells significantly increased and correlated with advanced stage of the disease [32]. In a different setting than cancer, activated T cells with high CD39 expression were prone to apoptosis in older individuals and suggested that CD4 + CD39 + effector T cells do not develop into long-lived memory cells [33].…”
Section: Discussionmentioning
confidence: 99%